(untitled) (Світ фінансів, 2017)
Крисоватий А. І. Аксіоми суспільного вибору в податкових фінансах. Розкрито сутністні ознаки фіскальної соціології як складової вчення про психологію податкових фінансів держави. Визначено теоретико-організаційні підвалини щодо обгрунтування проблеми фіскального вибору. Виокремлено окремі положення теорії суспільного вибору для формування партнерських стосунків у царині податкової політики. Krysovatyy A. Axioms of public choice in tax finances. The essence signs of fiscal sociology as constituent of studies about psychology of tax finances of the stateare exposed in the article. Theoretical-organizational foundations as for the grounding of the problem of fiscal choice are determined. Separate positions of the theory of public choice for forming of partners relations in the sphere of tax policy are selected.